Time-motion analysis of the 2023 Women`s World Boxing Championships finals - Martusciello, F.; Perazzetti, A.; Kaçurri, A.; Consolati, M.; Tessitore, A. (Sports, 2025)
Background: This study investigated boxers` activity profiles during the final matches (3 × 3 min format) of the IBA 2023 Women`s World Boxing Championships.